Student-Centered Learning in an EFL Classroom: A Case Study of an Indonesian Private School - Maura Madiniya; Dina Irmayanti; Rifqi Robbani; Dostiwi Dostiwi; Elsyam Maulana (International Journal of English and Applied Linguistics (IJEAL), 2026)
The purpose of this study was to evaluate how well student-centered learning (SCL) increases student engagement and participation in English language instruction. Through conversation, teamwork, and problem-solving exercises, student-directed learning places students as active participants in the learning process. A qualitative descriptive approach was used to investigate this study by using teacher and student interviews and classroom observations. The results showed that students exhibited behaviors consistent with student-centered learning, such as participating in teacher-centered questions and actively participating in peer conversations. The study emphasizes how the use of SCL encourages increased student participation, independence, and the growth of communication and critical thinking abilities. These findings highlight the potential of student-centered learning as a successful teaching method for English learning.